Awareness Learning Metacognitive And Critical Thinking Skill Senior High School Students Through Problem-Based Learning Combined With STEM (Journal of Namibian Studies : History Politics Culture, 2023)
Awareness Learning Metacognitory (ALM) and thinking skills are the dimensions of knowledge and skills that each student should have on each level of education in Indonesia. Quantitative research using quasi-experimental methods aims to describe three things: the critical thinking abilities of biology-based senior high school students, and the critical thinking abilities of gender-based senior high school students, and the ALM senior high school students' critical thinking abilities through PBLs integrated with STEM. This study employs the Nonequivalent Control-Group Design. This study's sample consists of 220 students from seven classes at XI SMAN Model Terpadu Madani Palu in Indonesia.The researchers choose 64 students from two classes as sample. The researchers consider the homogeneity of students and their cognitive abilities in two classes. Hence, the researchers apply purposive sampling. Critical thinking skills data obtained through 12 reasoned multiple choice questions and ALM data obtained through questionnaire consisting of 30 questions. The outcomes showed that PBL joined with STEM fundamentally affected the decisive reasoning abilities of senior secondary school understudies in Science subjects contrasted with customary learning, even though gender was not affected by the PBL combined with STEM model. In addition, PBL combined with STEM has a significant effect on ALM. 87.5% of students who have ALM are in the good category and 12.5% ​​is quite good. All ALM indicators are in good category except for Information Management Strategies which are in good category.